Marketing communication through the integration of new media and traditional media : the insights. - Adzharuddin, Nor Azura (Vasile Goldis Western University, Arad, 2012)
The paper demonstrates the current trend of advertising research that has moved towards integrating two or more media using both the traditional media and the new media. Recent advertising researches have shown that the repetition of a particular advertising feature across two different media has been found to reinforce the effectiveness of marketing communication. It has also been proven influential in improving memory and the attitude of consumers. Based on the positive and encouraging recent findings, more studies should focus on examining advertising effects using the integration of the traditional medium (television) and the new medium (the Internet). Bearing in mind that the position of the Internet have progressed rapidly in the past, it is possible that the Internet can play a major role in advertising, going hand in hand with the traditional medium especially television.